Use of ladle furnace slag containing heavy metals as a binding material in civil engineering - Xu, Bo (2021)
The disposal of ladle furnace slag (ladle slag, LS) containing traces of heavy metals produced during steelmaking has become an environmental issue. The use of LS as a binding material in civil engineering is a potential solution. In this context, this study firstly attempted to activate LS with sodium hydroxide (NaOH), sodium sulfate (Na2SO4), and sodium metasilicate (Na2SiO3), and then blended it with ground granulated blast-furnace slag (GGBS) with different LS:GGBS ratios. The chemical-activated LS pastes and LS-GGBS pastes were cured for different ages, and then subjected to a compressive strength test. The results indicated NaOH, Na2SO4, and Na2SiO3 could not effectively activate this LS, with 28-day strength <2 MPa, whilst the LS-GGBS yielded much higher strength, up to 15.6 MPa at 28 days. Only a very low concentration of Pb leached out from the LS-GGBS at 14 days, and none of the possible heavy metals were detected at 56 days. This indicates that LS-GGBS can be potentially used as a binding material in civil engineering. The X-ray diffraction (XRD) revealed that the Ca(OH)2 in LS acted as the main activator for GGBS hydration; the MgO and CaCO3 in LS seemed to play similar roles as that of the Ca(OH)2. The XRD, thermogravimetric analysis (TGA), fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), and energy dispersive X-ray spectroscopy (EDX) indicated that the main hydration product of LS-GGBS was calcium silicate hydrates (CSH).